Strain sensor based on FBG in fiber loop ring down system. Issue 9 (6th June 2022) - Wu, Kai; Zhao, Chunliu; Mao, Bangning; Kang, Juan; Gong, Huaping; Wang, Hailong; Wang, Dongning
Abstract: In this paper, a strain sensor with a high resolution based on fiber Bragg grating (FBG) is proposed by combining a fiber loop ring down (FLRD) technology. When a light pulse enters and circulates in the fiber loop, it experiences a little loss each time as it paases through the sensor head. The ring‐dong time of the system would be altered by intensity loss near the sensor head, which is related to the size of the strain. The experimental results show that the FBG strain sensor with a high resolution is achieved by monitoring the ring‐down time, due to the more precision time measurement compared with the wavelength measurement. In the 0–1250 με strain range, the sensitivity ranged from 5.82 to 20.82 ns/με, and the theoretical best resolution is obtained as 0.24 με. The system has the advantages of simple structure, low cost, reflective sensor head, and high resolution.